FUNCTION AND DYNAMICS OF DETAILS IN ABDULLA QAHHOR'S NOVEL "SAROB" (Scientific journal of the Fergana State University, 2024)
This article talks about the detailed function and dynamics in the novel “Mirage” by Abdullah Kakhhor, a watchmaker of words who has won a place in Uzbek literature. This theoretical problem is analyzed and scientific and theoretical conclusions are drawn using the example of the novel “Mirage”.